Indigenous and Traditional Management Creates and Maintains the Diversity of Ecosystems of South American Tropical Savannas - Ferreira, Maria Julia; Levis, Carolina; Chaves, Leonardo; Clement, Charles Roland; Soldati, Gustavo Taboada (Frontiers in Environmental Science, 2022)
The tropical South American savannas have been occupied and manipulated by humans since the late Pleistocene. Ecologists consider that soils, hydrology, and seasonal precipitation influence the structure and composition of plants and the fire-proneness of savannas. However, the human influence on these dynamics remains uncertain. This is because little is known about human activities and what influence they have on the diversity of ecosystems. Considering this, our study sought to synthesize the management practices used by small-scale societies of the South American savannas, compile the species that are the focus of direct management, and demonstrate the role of this management in maintaining the diverse ecosystems that make up the savannas. We also set out to test the hypotheses that forms of management differ depending on the ecosystem and cultural matrices. To do so, we conducted a systematic review, in which we collected 51 articles with information about the management carried out by small-scale societies. From this, we categorized 10 management practices directed to ecosystems: protection of the ecosystem, enrichment of species, topographic changes, increased soil fertility, cleaning, prevention of fire, resource promotion, driving of game, swidden-fallow, and maintenance of ecosystem structure. We identified 19 native plant species whose populations are managed in-situ. These management practices have proven capable of keeping savanna and grassland ecosystems open and increasing the occurrence of forest ecosystems in the mosaic, as well as favoring plants of human interest in general. We note that there is a relationship between management practices with ecosystems and cultures, which suggests that both factors influence the management of landscapes. We conclude that management practices of small-scale societies are responsible for domesticating South American tropical savannas and that these savannas are composed of a mosaic of culturally constructed niches. The small-scale societies that inhabit these environments have important traditional ecological knowledge and strategies that enable the use, conservation, and restoration of savannas, extremely threatened by agribusiness today.